Exploitation of Endophytic Bacteria to Enhance the Phytoremediation Potential of the Wetland Helophyte Juncus acutus - Syranidou, Evdokia; Christofilopoulos, Stavros; Gkavrou, Georgia; Thijs, Sofie; Weyens, Nele; Vangronsveld, Jaco; Kalogerakis, Nicolas (Frontiers in Microbiology, 2016)
This study investigated the potential of indigenous endophytic bacteria to improve the efficiency of the wetland helophyte Juncus acutus to deal with a mixed pollution consisting of emerging organic contaminants and metals. The beneficial effect of bioaugmentation with selected endophytic bacteria was more prominent in case of high contamination: most of the inoculated plants (especially those inoculated with the mixed culture) removed higher percentages of organics and metals from the liquid phase in shorter times compared to the non-inoculated plants without exhibiting significant oxidative stress. When exposed to the lower concentrations, the tailored mixed culture enhanced the performance of the plants to decrease the organics and metals from the water. The composition of the root endophytic community changed in response to increased levels of contaminants while the inoculated bacteria did not modify the community structure. Our results indicate that the synergistic relationships between endophytes and the macrophyte enhance plants’ performance and may be exploited in constructed wetlands treating water with mixed contaminations. Taking into account that the concentrations of emerging organic contaminants used in this study are much higher than the average contents of typical wastewaters, we can conclude that the macrophyte J. acutus with the aid of a mixed culture of tailored endophytic bacteria represents a suitable environmentally friendly alternative for treating pharmaceuticals and metals.